Industrial and Labor Relations Terms : A Glossary - Doherty, Robert W. (Book collections on Project MUSE., 2018)
A popular reference book, this bulletin gives definitions and historical background for nearly 300 frequently used words, phrases, and acronyms. It has been revised to reflect recent developments in labor relations and is extensively cross-referenced.